MODIFICATION OF DOMINO CARD GAME AS AN ALTERNATIVE TO THE INTRODUCTION OF LETTERS FOR EARLY AGE CHILDREN - Eneng Yuli; Iwan Ruswandy (IKIP Siliwangi Bandung, 2019)
Teaching children to recognize letters is not an easy thing to do, not a few parents and early childhood educators need more patience to introduce letters, introducing letters to children is difficult enough especially to teach them reading. Children are unique and play is their world, but there are few of schools that introduce letters to children by generalizing all children with minimal use of media so that makes children become easily bored when learning and it is difficult to understand the learning given. Domino card game is a game that played by almost all ages and also the rules of the game are easy to understand and have an element of entertainment. This domino card game is suitable to be used as a learning media in introducing letters to early age children. Through a modification that can adjust to the children’s needs in recognizing letters i.e. the changes that occur in the symbols of dots on both sides of the domino card that change into one side containing letters and the other side containing images that are equipped with rules that are easily understood by children as well as attractive card designs so that they can make this card game as a medium for early age children recognize the letters so that learning becomes fun, so that children can easily understand the material and learning objectives can be achieved. This study uses a qualitative approach and concept analysis methods. Every child has a different comprehension and learning style and children also need time to be able to move their entire body so they can explore their environment as a whole, so that they don't get bored or burdened when the learning process takes place. Through this modified domino card, the researcher then names the game with